Bibliometric Analysis of Development Maps and Research Directions (Sustainable Finance) in the Scopus Database (2002-2025) - Mahening, Deseva Raras; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to map the developments, trends, and directions of research in the field of Sustainable Finance through a bibliometric approach to scientific publications indexed in the Scopus database in the period 2002–2025. The increasing global attention to sustainability issues and the integration of environmental, social, and governance (ESG) aspects in the financial system make this study important to understand the dynamics and structure of Sustainable Finance research scientifically. Bibliometric analysis was carried out using VOSviewer and Microsoft Excel on bibliographic data which included the number of publications per year, geographical distribution, institutional affiliation, author collaboration, journal sources, and thematic mapping based on keywords. The results of the analysis show a significant increase in the number of Sustainable Finance research publications since 2015, with the peak of the publication trend occurring in the period 2018–2025. Geographically, Malaysia and Indonesia are recorded as the countries with the highest publication contributions. Institutionally, International Islamic University Malaysia was the most prolific affiliate, while authors such as Hassan, M.K. and Zain, N.R.M. emerged as major contributors. In addition, thematic mapping reveals that Islamic finance, sustainable finance, ethical investment, and circular economy are the dominant themes in the Sustainable Finance research landscape. This research makes an original contribution by presenting a comprehensive overview of the structure, collaboration patterns, and thematic development of Sustainable Finance research in the long term. The findings of this research can be used by researchers as a basis for identifying research gaps and future research directions, as well as by policymakers and practitioners as a reference in formulating sustainable financial strategies and policies based on scientific evidence.